Susan Stebbing - Janssen-Lauret, Frederique 1985- (Cambridge University Press, 2022)
Susan Stebbing (1885-1943), the UK's first female professor of philosophy, was a key figure in the development of analytic philosophy. Stebbing wrote the world's first accessible book on the new polyadic logic and its philosophy. She made major contributions to the philosophy of science, metaphysics, philosophical logic, critical thinking and applied philosophy. Nonetheless she has remained largely neglected by historians of analytic philosophy. This Element provides a thorough yet accessible overview of Stebbing's positive, original contributions, including her solution to the paradox of analysis, her account of the relation of sense data to physical objects, and her anti- idealist interpretation of the new Einsteinian physics. Stebbing's innovative work in these and other areas helped move analytic philosophy from its early phase to its middle period
Title from publisher's bibliographic system (viewed on 18 Nov 2022)
Keywords: Stebbing, L. Susan / (Lizzie Susan) / 1885-1943; Stebbing, L. Susan -- 1885-1943; Women philosophers / Great Britain